KNOWLEDGE AND UNDERSTANDING OF THE PEOPLE'S DEMOCRACY IN OPERATION OF WANGPONG PROVINCIAL ADMINISTRATION ORGANIZATION, PRANBURI DISTRIC, PRACHUAP KHIRI KHAN PROVINCE - Sutanon, Sanhapak; Kettong, Dawnapa; Bhalakula, Anucha (Journal of MCU Phetchaburi Review, 2025)
This mixed-method research aimed to 1) study the level of knowledge and understanding of democracy among the people; 2) study the relationship between the 6 Saraniyadhamma principles and the people's knowledge and understanding of democracy; and 3) present the people's knowledge and understanding of democracy by applying the 6 Saraniyadhamma principles. The sample consisted of 388 people in Wang Pong Subdistrict Administrative Organization, Pran Buri District, Prachuap Khiri Khan Province, aged 18 years and over, and 9 key informants. Data were analyzed by percentage, mean, standard deviation, Pearson's product moment correlation coefficient, and descriptive content analysis. The results showed that 1) the overall level of knowledge and understanding of democracy among the people was at a high level; 2) the Saraniyadhamma principles were positively and highly correlated with the people's knowledge and understanding of democracy in the operation of Wang Pong Subdistrict Administrative Organization, Pran Buri District, Prachuap Khiri Khan Province; and 3) the people's knowledge and understanding of democracy by applying the 6 Saraniyadhamma principles, namely: 1) Metta-kaya-karma 2) Kindness in speech, communicate with understanding. 3) Kindness in thought, respect for others' thoughts. 4) Public welfare, consider the common good. 5) Morality, know roles and duties. 6) Ditthi, believe in common principles. Apply them to create knowledge and understanding of the democratic system for the people so that they respect the rights, freedoms, and equality of themselves and others, as well as be eager to participate in various activities, know their rights and duties under a democratic system, and express their political opinions appropriately.